Studies Involving a Commercial Extract of Three Ballerina: ii- Evaluation of the in Vitro Effect on the Labeling of Blood Constituents of rats with Technetium-99m and on the Morphology of the Red Blood Cell - Nelson de Souza Pinto, Lúcia de Fátima Amorim, Dulciane Nunes Paiva, Vilma Gomes Barreto, Gláucio Diré & , Sebastião David Santos-Filho, Mario Bernardo-Filho (Journal of Applied Pharmaceutical Science, 2013)
The aim of this work is to characterize (electric conductivity and refractive index) a Three Ballerina (TB) and to evaluate its in vitro effect on the labeling of blood constituents with 99mTc and on the morphology of the red blood cells (RBC). Anticoagulated whole blood (Wistar rat) was incubated with a TB extract and the labeling of the blood constituents with technetium-99m (99mTc) was performed. Plasma (P) and blood cells (BC) were isolated and aliquots were also precipitated with trichloroacetic acid to separate soluble (SF) and insoluble fractions (IF). The %ATI in these samples was calculated. The morphology of the treated RBC showed no shape’s qualitative alterations. The TB extract was characterized with an electric conductivity of 1.35±0.04mSv/cm and refractive index of 2.21±0.15%BRIX. TB extract decreased significantly (p
Keywords: Blood constituents, technetium-99m, red blood cell, Three ballerina, electric conductivity, refractive index.